2016
DOI: 10.1080/0142159x.2017.1270437
|View full text |Cite
|
Sign up to set email alerts
|

Measuring professional identity formation early in medical school

Abstract: These PIF scores distributed similarly to novice students in other professions. Developmental-theory based PIF and moral reasoning measures are related. Students reflected on these measures in meaningful ways suggesting utility of measuring PIF scores in medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 32 publications
0
73
0
9
Order By: Relevance
“…Previously, we demonstrated 1) evidence for internal structure (inter-and intra-rater reliability of the staging of the PIE), 2) a positive and significant relationship to the Defining Issues Test 2, a validated measure of moral reasoning which is a theoretically related variable, and 3) evidence that students completing these essays and reflecting on the feedback from them understood the construct of PIF underlying this framework-suggesting response process validity evidence as described in the Messick validity model (Cook & Beckman, 2006;A. Kalet et al, 2017).…”
Section: Future Directionsmentioning
confidence: 72%
See 1 more Smart Citation
“…Previously, we demonstrated 1) evidence for internal structure (inter-and intra-rater reliability of the staging of the PIE), 2) a positive and significant relationship to the Defining Issues Test 2, a validated measure of moral reasoning which is a theoretically related variable, and 3) evidence that students completing these essays and reflecting on the feedback from them understood the construct of PIF underlying this framework-suggesting response process validity evidence as described in the Messick validity model (Cook & Beckman, 2006;A. Kalet et al, 2017).…”
Section: Future Directionsmentioning
confidence: 72%
“…We have previously reported that PIE stage scores from entering medical students 1) distributed similarly to those of age-matched students in other professions, and 2) students found these scores meaningful, suggesting there could be utility in measuring PIF scores in medical education (A. Kalet et al, 2017).…”
Section: Measuring Pifmentioning
confidence: 91%
“…We examined several existing theories (professional identity formation, ego development, goal orientation and feedback seeking, and self‐determination theory) for their possible fit with our data. We determined that stages of human motivation explained our findings best by re‐reading each interview transcript and characterising each participant from that perspective.…”
Section: Methodsmentioning
confidence: 99%
“…Aside from these questions, students were asked to submit the professional identity essay (PIE) proposed by Kalet et al [28] three times. PIE is useful for helping learners articulate their values and norms about medical professionalism, and teachers provide feedback by referring to rubrics based on Kegan's constructive developmental theory [28,29]. This study used a Japanese version of PIE (PIE-J) as a reference for mentors' feedback on Q1-3 and as an assessment tool for students' PIF levels (see also Instruments).…”
Section: Q3mentioning
confidence: 99%